New records of South American sea lion Otaria flavescens predation on southern rockhopper penguins Eudyptes chrysocome at Staten Island, Argentina - Raya Rey, Andrea Nélida; Saenz Samaniego, Ricardo Andres; Petracci, Pablo Fabricio (Polar Biology)
Predation by fur seals and sea lions has been identified, among others, as a potential cause of the declines in rockhopper penguin populations. Here, we report a multiple predation event of southern rockhopper penguins Eudyptes chrysocome by South American sub-adult male sea lions Otaria flavescens at Staten Island, Argentina. The sea lions attacked and preyed on penguins mostly using a wait and rush tactic at sea, but in some cases, penguins were also pursued on land. Although observations suggested that only a few sea lions are involved in predation, further research is necessary to elucidate the importance of this predation in the rate of population decline. Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Saenz Samaniego, Ricardo Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Petracci, Pablo Fabricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Área Zoología; Argentina